Translocation and activation of sphingosine kinase 1 by ceramide‐1‐phosphate. Issue 4 (15th November 2018) - Nishino, Shohei; Yamashita, Hisahiro; Tamori, Mizuki; Mashimo, Masato; Yamagata, Kazuyuki; Nakamura, Hiroyuki; Murayama, Toshihiko
Abstract: Sphingosine kinases (SphKs) and ceramide kinase (CerK) phosphorylate sphingosine to sphingosine‐1‐phosphate (S1P) and ceramide to ceramide‐1‐phosphate (C1P), respectively. S1P and C1P are bioactive lipids that regulate cell fate/function and human health/diseases. The translocation and activity of SphK1 are regulated by its phosphorylation of Ser 225 and by anionic lipids such as phosphatidic acid and phosphatidylserine. However, the roles of another anionic lipid C1P on SphK1 functions have not yet been elucidated, thus, we here investigated the regulation of SphK1 by CerK/C1P. C1P concentration dependently bound with and activated recombinant human SphK1. The inhibition of CerK reduced the phorbol 12‐myristate 13‐acetate‐induced translocation of SphK1 to the plasma membrane (PM) and activation of the enzyme in membrane fractions of cells. A treatment with C1P translocated wild‐type SphK1, but not the SphK1‐S225A mutant, to the PM without affecting phosphorylation signaling. A cationic RxRH sequence is proposed to be a C1P‐binding motif in α‐type cytosolic phospholipase A 2 and tumor necrosis factor α‐converting enzyme. The mutation of four cationic amino acids to Ala in the 56‐RRNHAR‐61 domain in SphK1 reduced the phorbol 12‐myristate 13‐acetate‐ and C1P‐induced translocation of SphK1 to the PM, however, the capacity of C1P to bind with and activate SphK1 was not affected by this mutation. In conclusion, C1P modulates SphK1 functions by interacting with multiple sites in SphK1. Abstract : Sphingosine kinases (SphKs) and ceramide kinase (CerK) phosphorylate sphingosine to sphingosine‐1‐phosphate (S1P) and ceramide to ceramide‐1‐phosphate (C1P), respectively. In the current study, we found that C1P modulates SphK1 functions by interacting with multiple sites in SphK1.